Pedagogy approaches and teaching strategies for innovative teaching - Alias, Nurul Fitriah; Kamarudin, Nurzatulshima (Faculty of Educational Studies, Universiti Putra Malaysia, 2013)
Innovation in teaching and learning has become a significant growth area in recent years. Innovative teaching strategies have evolved to transform the way teachers teach from the traditional 'chalk and talk' method to creative and lively teaching methods. The use of innovative methods in teaching has been proven to be more effective learning tools in enhancing teaching and learning and improving students' motivation in learning and their academic performance. Therefore, this calls for a paradigm shift from lecture-based method to active learning strategies that focus on effective teaching and promote creative and critical thinking among the students. This concept paper seeks to inform and suggest useful innovative teaching strategies that can be employed in imparting knowledge to the students namely problem based learning and cooperative learning.